Makna Tijarah Dalam Tafsir Ayat Dan Hadits Ekonomi Serta Penerapannya Dalam Praktik Bisnis Islam - Sobarna, Nanang; Ridwan, Ahmad Hasan (Eco-Iqtishodi : Jurnal Ilmiah Ekonomi dan Keuangan Syariah, 2024)
The meaning of tijarah in the Qur'an is often interpreted as trade, commerce, business or buying and selling. The term tijarah in the Qur'an is often expressed to provide understanding or guidance for conducting commerce or business in Islam. So the aim of this research is to understand the meaning of tijarah in the Al-Qur'an, which then applies this interpretation to Islamic business practices. The method used in this research is a qualitative method with a literature study approach. The results of this research show that the word tijarah in the Al-Qur'an, along with all its derivatives, is repeated eight times, found in Surah Al-Baqarah/2: 16 and 282, An-Nisa/4: 29, At-Taubah/9 : 24, An-Nur/24: 37, Fathir/35: 29, Ash-Shaf/61: 10, and Al-Jumu'ah/62: 11, which shows the meaning of commerce or business in material and immaterial forms. The meaning of tijarah in the Al-Quran provides understanding and guidance that business or commerce practices should be carried out in accordance with the Shari'a by avoiding anything that justifies any means just to gain profit. However, the most important thing is to pursue pleasure to get blessings from the sustenance given by Allah SWT.